Case report: De novo SAMD9L truncation causes neonatal-onset autoinflammatory syndrome which was successfully treated with hematopoietic stem cell transplantation - Caldirola, María Soledad; Seminario, Analía Gisela; Luna, Paula Carolina; Curciarello, Renata; Docena, Guillermo Horacio; Fernandez Escobar, Nicolás; Drelichman, Guillermo; Gattorno, Marco; de Jesus, Adriana A.; Goldbach-Mansky, Raphaela; Gaillard, María Isabel; Bezrodnik, Liliana (Frontiers in Pediatrics, 2023)
During the recent years the identification of monogenic mutations that cause sterile inflammation has expanded the spectrum of autoinflammatory diseases, clinical disorders characterized by uncontrolled systemic and organ-specific inflammation that, in some cases, can mirror infectious conditions. Early studies support the concept of innate immune dysregulation with a predominance of myeloid effector cells dysregulation particularly neutrophils and macrophages in causing the tissue inflammation. However, recent discoveries have shown a complex overlap of features of autoinflammation and/or immunodeficiency contributing severe disease phenotypes. Here, we describe the first Argentine patient with a newly described frameshift mutation in SAMD9L c.2666delT/p.F889Sfs*2 presenting with a complex phenotypic overlap of CANDLE-like features and severe infections-induced cytopenias and immunodeficiency. The patient underwent a fully matched unrelated HSCT and has since been in inflammatory remission five years post- HSCT.